Treatments for inferior alveolar nerve paresthesia associated with third molar extraction (Research, Society and Development, 2025)
This study aimed to identify the causes, risk factors, and treatment strategies for inferior alveolar nerve paresthesia associated with third molar extraction. A descriptive and qualitative literature review was conducted, with a survey of publications in the PubMed, Scielo, and Google Scholar databases, prioritizing articles and books published between 2019 and 2025. The analysis showed that anatomical aspects, age, gender, surgical technique, and duration of the procedure are factors that influence the incidence of nerve injuries. The results indicated that preventive measures, such as adequate surgical planning and the use of imaging tests, are essential to minimize neurological damage. In addition, therapeutic options, such as drug therapies with vitamins and corticosteroids, laser therapy, acupuncture, and, in more severe cases, microsurgical techniques, have demonstrated efficacy in sensory recovery. It is concluded that a preventive approach and individualized management are essential to reduce complications and promote functional rehabilitation, reinforcing the importance of technical and scientific knowledge for safe and quality dental care.